Proceedings of the 9th ACM Conference on Creativity &Amp; Cognition 2013
DOI: 10.1145/2466627.2466666
|View full text |Cite
|
Sign up to set email alerts
|

Empowering cognitive fixedness

Abstract: Our goal was to understand potential aspects of cognitive fixedness in people who possess traditional viewpoints. We conducted an experiment that involved design training (in-studio design and creativity training). We observed several stages of idea generation during which artisans generated ideas for new design of traditional wooden sandals. During the first stage, artisans were challenged to generate ideas at extreme levels based on their prior knowledge. We examined their conceptual sketches and verbalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Fauconnier and Turner's (2008) conceptual blending analyses how people combine perceptual, experiential and conceptual aspects of different concepts subconsciously to generate new insights (Fauconnier and Turner, 2008). The recent study of Nagai and Junaidy (2013) argues that the ability to capture and utilise stimuli during extreme levels of cognitive fixedness that produce conflicts of stimuli may lead to unconventional ways of thinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fauconnier and Turner's (2008) conceptual blending analyses how people combine perceptual, experiential and conceptual aspects of different concepts subconsciously to generate new insights (Fauconnier and Turner, 2008). The recent study of Nagai and Junaidy (2013) argues that the ability to capture and utilise stimuli during extreme levels of cognitive fixedness that produce conflicts of stimuli may lead to unconventional ways of thinking.…”
Section: Discussionmentioning
confidence: 99%
“…With a high level of mastery, an individual like a craftsperson is often recognised for his/her traditional viewpoints that may be structured by prior knowledge and typical features contained in familiar categories (Finke, 1996). The recent study of Nagai and Junaidy (2013) demonstrated that the craftsmen's conceptualisation at the early stage of idea generation experiences a fixation that disables them from exploring the abstract realm which normally occurs at the early stage of idea generation. This explains that the craftsman's conceptualisation, seen at the early stage, has evidently occurred at the later stage of idea generation .…”
Section: Conceptual Ideation Of a Craftsmanmentioning
confidence: 99%
“…Our recent study demonstrated that artisans' ability to capture and utilize stimuli during extreme levels of cognitive fixedness might lead to unconventional ways of thinking [4,5]. However, empowering this cognitive fixedness is definitely not a standalone activity.…”
Section: Traditional Artisans and Cognitive Fixednessmentioning
confidence: 99%
“…So far, a system to support divergent thinking was proposed which was also effective to the designers [1]. Also, cognitive features of the designers and systems to support the, at the initial stage of the conceptual product design were proposed [2,3]. Those previous studies showed valuable suggestions and applicability for considering effective support systems or tools for enhancing creativity of the product designers.…”
Section: Introductionmentioning
confidence: 99%